Representasi Komunikasi Politik Pada Video Epic Rap Battle Of Presidency 2024 - Prayoga, Billy; Wiryany, Detya; Meltareza, Ridma (AGUNA: Jurnal Ilmu Komunikasi, 2025)
This study aims to analyze the semiotics in the video "Epic Rap Battle of Presidency 2024" by SkinnyIndonesia24. It employs John Fiske's semiotic analysis method to examine three social codes within the video: the level of reality, representation, and ideology. The main objective of this research is to understand how political messages are conveyed through entertainment media in the digital era, particularly through YouTube, which plays a significant role in the dissemination and influence of political messages. The research method involves semiotic analysis to explore the signs and meanings contained in the video. By focusing on aspects of reality, representation, and ideology, this study reveals how political identities are represented and perceived by the audience. The findings show that the video "Epic Rap Battle of Presidency 2024" uses various cinematographic techniques and symbols to convey political messages. Political reality is depicted through subjective portrayals of political victory, representation is reinforced with the use of close-ups to emphasize expressions and gestures, while ideology is presented through narratives of individualism and criticism of the existing political system.